Direct inhibitors of InhA active against Mycobacterium tuberculosis - Manjunatha, Ujjini H. (Sci Transl Med, 2015)
New chemotherapeutic agents are urgently required to combat the global spread of multi-drug resistant tuberculosis (MDR-TB). The mycobacterial enoyl reductase, InhA, is one of the few clinically-validated targets in tuberculosis drug discovery. Here, we report the identification of a new class of direct InhA inhibitors, the 4-hydroxy-2-pyridones, using phenotypic high-throughput whole-cell screening. This class of orally-active compounds showed potent bactericidal activity against common isoniazid-resistant TB clinical isolates. Biophysical studies revealed that 4-hydroxy-2-pyridones bound specifically to InhA in an NADH-dependent manner and blocked the enoyl-substrate binding pocket. The lead compound NITD-916 directly blocked InhA in a dose-dependent manner and showed in vivo efficacy in acute and established mouse models of infection by Mycobacterium tuberculosis. Collectively, our structural and biochemical data open up new avenues for rational structure-guided optimization of the 4-hydroxy-2-pyridone class of compounds for the treatment of MDR-TB.